2022
DOI: 10.1017/s104795112100500x
|View full text |Cite
|
Sign up to set email alerts
|

Condition notification assisted by virtual reality technology reduces the anxiety levels of parents of children with simple CHD: a prospective randomised controlled study

Abstract: Purpose: This study explored the effects of condition notification based on virtual reality technology on the anxiety levels of parents of children with simple CHD. Methods: The subjects of the study were the parents of 60 children with simple CHD who were treated in our centre. The state anxiety scale was used to assess the anxiety status of the parents of the children before and after the condition notification in different ways (based on virtual reality explanations and written explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…But more research is needed E a r l y b i r d in order to determine if it may occur and what approach to pain and anxiety, for example, in intensive care units [46]. VR also allows you to effectively reduce preoperative anxiety without the use of pharmacological agents [1,29,94]. Studies have observed the effect of using VR for postoperative rehabilitation on reducing the use of analgesics in hospitals [57,85].…”
Section: Vr-based Pain Management During Cardiac Surgerymentioning
confidence: 99%
“…But more research is needed E a r l y b i r d in order to determine if it may occur and what approach to pain and anxiety, for example, in intensive care units [46]. VR also allows you to effectively reduce preoperative anxiety without the use of pharmacological agents [1,29,94]. Studies have observed the effect of using VR for postoperative rehabilitation on reducing the use of analgesics in hospitals [57,85].…”
Section: Vr-based Pain Management During Cardiac Surgerymentioning
confidence: 99%
“…With its ability to transport users to different dimensions through immersive and captivating situations, VR has become an effective method in the relief of stress for users. It can temporarily distract people from real-life problems by granting them a sensation of presence in a computer-generated world [ 7 ]. Because VR is immersive, it stimulates a variety of senses and produces an engrossing experience that can induce calm and happy feelings.…”
Section: Introductionmentioning
confidence: 99%